Strategi Guru Dalam Menstimulasi Kecerdasan Finansial Sejak Dini: Systematic Literature Review - Firdaus, Umi Risatul; Rohmah, Lailatu; Munastiwi, Erni (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2024)
This project aimed to find and evaluate successful ways to teach financial literacy to Indonesian children in their early years. The main problem in this study was children's lack of knowledge about basic economic concepts, which can impact their future ability to manage resources. This study used the Systematic Literature Review (SLR) method throughout the study's planning, implementation, and reporting stages. To collect literature sources four databases were used: Google Scholar, Open Knowledge, Sage, and Science Direct. The literature used as research material was selected based on inclusion and exclusion criteria to improve the quality and relevance of the evidence used in the study, ensuring that the findings obtained were robust and credible. The findings of this study indicate that the use of direct strategies, the use of educational media and games, the habit of saving, and a combination of strategies have helped improve children’s understanding of financial literacy. Collaboration between teachers and parents is essential to teach financial literacy. The findings of this study highlight the importance of incorporating financial literacy into the Indonesian education curriculum, with the help of appropriate media and child-based learning, as well as the need for strong collaboration between schools and parents to create a conducive environment for the development of children’s financial skills.